2019
DOI: 10.3390/agronomy9010016
|View full text |Cite
|
Sign up to set email alerts
|

Weather During Key Growth Stages Explains Grain Quality and Yield of Maize

Abstract: Maize (Zea mays L.) grain yield and compositional quality are interrelated and are highly influenced by environmental factors such as temperature, total precipitation, and soil water storage. Our aim was to develop a regression model to account for this relationship among grain yield and compositional quality traits across a large geographical region. Three key growth periods were used to develop algorithms based on the week of emergence, the week of 50% silking, and the week of maturity that enabled collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…A moderate correlation was declared when 0.3 < |r| ≤ 0.7 and strong correlations when 0.7 < |r| ≤ 1.0. A threshold of |r| < 0.5 was used to exclude parameters from multiple linear regression following Wilmsmeyer et al [47]. Stepwise multiple linear regression (Proc Reg, STEPWISE, SAS, Cary NC) was used to investigate the factors that were significant in determining soybean seed yield and composition including genetic improvement rate (as year of release), [CO 2 ], and the climate parameters, pptn, average Tmax and average Tmin during the three phenological phases, V, FP, and SF.…”
Section: Methodsmentioning
confidence: 99%
“…A moderate correlation was declared when 0.3 < |r| ≤ 0.7 and strong correlations when 0.7 < |r| ≤ 1.0. A threshold of |r| < 0.5 was used to exclude parameters from multiple linear regression following Wilmsmeyer et al [47]. Stepwise multiple linear regression (Proc Reg, STEPWISE, SAS, Cary NC) was used to investigate the factors that were significant in determining soybean seed yield and composition including genetic improvement rate (as year of release), [CO 2 ], and the climate parameters, pptn, average Tmax and average Tmin during the three phenological phases, V, FP, and SF.…”
Section: Methodsmentioning
confidence: 99%
“…The highest relative humidity (74±1.73%) was found in the location maize after threshing. Determination of relative humidity and temperature in maize storage will help the trader to keep the quality and safety of raw materials for process controlling and food preservation (Butts-Wilmsmeyer et al, 2019;Palacious et al, 2019). Temperature and relative humidity are important factors in grain storage, due to its effect to EMC (Hanif et al, 2018).…”
Section: Environmental Conditionmentioning
confidence: 99%
“…Yield variability is not explained by rainfall in Bungoma probably because of sufficient soil moisture or rainfall. Water availability during anthesis and in the reproductive stage are found highly explanatory of grain yields (Armstrong, 1999;Butts-Wilmsmeyer et al, 2019). Since both water and temperature during anthesis and reproductive stage are known to affect yields, we conclude that sufficient water requirements could be the only reason why temperature indicators explain yields but not rainfall indicators.…”
Section: Research Questionsmentioning
confidence: 65%
“…In other studies however, water availability during anthesis and grain filling stage have been found highly ex-Chapter 4. Sensitivity and Predictability of Rain-fed Maize Yields to Growing Season Climate Indices: East Africa planatory of-and-results in high grain yield (Armstrong, 1999;Butts-Wilmsmeyer et al, 2019). Because both rainfall and temperatures are important in all stages of maize growth, we hypothesize that regionally varying sensitivities may be a function of other factors not examined such as soil characteristics and soil moisture availability during each phenological stage.…”
Section: Yield Explaining Climate Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation